Obstructive sleep apnea risk and determinant factors among type 2 diabetes mellitus patients at the chronic illness clinic of the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Worku, Abebe; Ayele, Eleni; Alemu, Shitaye; Legese, Gebrehiwot Lema; Yimam, Samrawit Meles; Kassaw, Getasew; Diress, Mengistie; Asres, Mezgebu Silamsaw (Frontiers in Endocrinology, 2023)
Introduction: Obstructive sleep apnea is a common sleep disorder among type 2 diabetes mellitus patients that has a deleterious effect on health with immediate and long-term impacts, such as daytime somnolence, headaches, increased risk of a stroke, increased risk of cardiac arrest, arrhythmias, hypertension, lost economic benefit. Despite its impact, data on the magnitude and associated factors of obstructive sleep apnea among type 2 diabetes mellitus patients in Ethiopia is still limited. Therefore, this study was done to determine the prevalence of high risk of obstructive sleep apnea and its associated factors among type 2 diabetes mellitus patients having follow-up at chronic follow-up clinic at University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2022. Methods: An institution-based cross-sectional study was employed. Data were collected using interviewer administered questionnaire and physical measurements with standard instruments. The collected data were entered into Epi data version 4.6 and exported into STATA 14 for analysis. Both Bivariate and multivariate binary logistic regression analyses were done to identify factors associated with high risk of obstructive sleep apnea. Variables with a p-value ≤0.05 in the multivariable logistic regression analysis were declared as significantly associated with high risk of obstructive sleep apnea. Results: A total of 319 type 2 diabetes mellitus patients with a median age of 58 years participated in this study. The overall prevalence of high risk of obstructive sleep apnea among the study participants was 31.97% (95%CI: 27.06%, 37.32%). On multivariable logistic analysis, neck circumference ≥ 40 centimeters (AOR=4.33, 95% CI 1.37, 13.72), physical inactivity (AOR=2.29, 95% CI 1.15, 4.53), comorbid hypertension (AOR=4.52, 95% CI 2.30, 9.18) and male gender (AOR=8.01, CI 95% 3.02, 21.24), were associated with high risk of obstructive sleep apnea. Conclusion and recommendation: The prevalence of high risk of obstructive sleep apnea among type 2 diabetes mellitus patients remains to be high. Neck circumference ≥ 40 centimeters, physical inactivity, comorbid hypertension and male gender were significantly associated with high risk of obstructive sleep apnea among type 2 diabetes mellitus patients. Screening and evaluation of type 2 diabetes mellitus patients for obstructive sleep apnea is recommended to avoid the negative impacts.